After the Fall: Awakening from the Dream in The Rider and Red Sparrow. (2nd October 2018) - Beck, Bernard
Abstract : Two recent movies, The Rider and Red Sparrow, are in contrast to a large number of movies celebrating the triumph of afflicted persons over obstacles that seem insurmountable. Through commitment, hard work, and determination, these characters are able to do the impossible. However, these two movies instead focus on the dire consequences of an inability to overcome obstacles. This change may reflect an increasing pessimism about current challenges and individuals' ability to meet them.